2014
DOI: 10.1007/s10571-014-0088-z
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Decline of Nogo-A Protein in the Mouse Cerebrum

Abstract: Nogo-A, a myelin-associated neurite growth inhibitory protein, is implicated in synaptic plasticity. It binds to its receptor namely the Nogo-66 receptor1 (NgR1) and regulates filamentous (F) actin dynamics via small GTPases of the Rho family, RhoA kinase (ROCK), LimK and cofilin. These proteins are associated with the structural plasticity, one of the components of synaptic plasticity, which is known to decline with normal aging. So, the level of Nogo-A and its receptor NgR1 are likely to vary during normal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…However, findings of post-mortem histological studies suggested, that it is rather the size than the number of the individual cells explaining the age-related decline of GM (Terry et al 1987;Peters et al 1998). At the molecular level the expression of NoGo-A, a myelin-associated neurite growth inhibitor protein decreases with age (Kumari and Thakur 2014). Recent results also imply the impact of aging on GM/ WM diffusion changes, explaining some cognitive variability and even decline (Salminen et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, findings of post-mortem histological studies suggested, that it is rather the size than the number of the individual cells explaining the age-related decline of GM (Terry et al 1987;Peters et al 1998). At the molecular level the expression of NoGo-A, a myelin-associated neurite growth inhibitor protein decreases with age (Kumari and Thakur 2014). Recent results also imply the impact of aging on GM/ WM diffusion changes, explaining some cognitive variability and even decline (Salminen et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Nogo-A is a myelin-associated neurite growth inhibitory protein, that binds to its receptor Nogo-66 receptor1 (NgR1) and regulates filamentous actin dynamics and involved in structural plasticity of the synapses. We demonstrated that Nogo-A protein level decreased in male and female forebrain of old mice while NgR1 remained unaltered [ 42 ]. In recent years, another set of synaptic proteins neurexins (Nrxns) and neuroligins (Nlgns) have emerged as potential candidates for alterations in structural synaptic plasticity.…”
Section: Synaptic Plasticity Genesmentioning
confidence: 99%
“…Few studies examined how age alters the expression of these proteins. Nogo-A levels are significantly decreased in aged animals (Trifunovski et al, 2006;Kumari and Thakur, 2014). A decrease in recovery is surprisingly observed in 12-month-old Nogo A/B deficient mice after TBI, compared to young adults, possibly related to hypomyelination (Marklund et al, 2009).…”
Section: Myelin Proteins and Constituentsmentioning
confidence: 93%